2013
DOI: 10.1124/dmd.113.051193
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Axitinib Interactions with Human Efflux and Hepatic Uptake Transporters: Implications for Disposition and Drug Interactions

Abstract: Axitinib is an inhibitor of tyrosine kinase vascular endothelin growth factor receptors 1, 2, and 3. The ATP-binding cassette (ABC) and solute carrier (SLC) transport properties of axitinib were determined in selected cellular systems. Axitinib exhibited high passive permeability in all cell lines evaluated (Papp ‡ 6 3 10 26 cm/s).Active efflux was observed in Caco-2 cells, and further evaluation in multidrug resistance gene 1 (MDR1) or breast cancer resistance protein (BCRP) transfected Madin-Darby canine kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 39 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…This may result in a considerable overestimation of the intestinal concentration, particularly for poorly soluble compounds. Other groups have used fraction absorbed, absorption rate, and enterocyte blood flow, as well as built-in functions in physiologically-based pharmacokinetic (PBPK) models to estimate gut concentrations (Agarwal et al, 2013;Reyner et al, 2013). Further exploring the caveats of the static model, three main assumptions should be mentioned: 1) the victim drug absorption, elimination or brain distribution is driven by a single pathway; 2) the neglect of the dynamic nature of the involved processes; and 3) the intestinal, plasma, and extracellular concentrations used ( [I 2 ], [I 1 ], or IC 50 ) do not correspond to the intracellular MDR1 binding site.…”
mentioning
confidence: 99%
“…This may result in a considerable overestimation of the intestinal concentration, particularly for poorly soluble compounds. Other groups have used fraction absorbed, absorption rate, and enterocyte blood flow, as well as built-in functions in physiologically-based pharmacokinetic (PBPK) models to estimate gut concentrations (Agarwal et al, 2013;Reyner et al, 2013). Further exploring the caveats of the static model, three main assumptions should be mentioned: 1) the victim drug absorption, elimination or brain distribution is driven by a single pathway; 2) the neglect of the dynamic nature of the involved processes; and 3) the intestinal, plasma, and extracellular concentrations used ( [I 2 ], [I 1 ], or IC 50 ) do not correspond to the intracellular MDR1 binding site.…”
mentioning
confidence: 99%
“…In particular, equilibrium was established in buffer-buffer and HLM-HLM controls for dialysis times ranging from 3 to 24 hours only with pazopanib, irrespective of whether we used conventional equilibrium dialysis (employing dialysis cells) or a commercial rapid equilibrium dialysis (RED) device. It has been reported that axitinib forms a supersaturated solution in buffers containing 0.5 or 1% dimethylsulfoxide (DMSO) (Reyner et al, 2013), and we surmised a similar situation may occur more generally with TKIs during the course of equilibrium dialysis experiments. Thus, we explored the use of a number of detergents to retain TKIs in solution without disrupting microsomal binding.…”
Section: Introductionmentioning
confidence: 57%
“…Furthermore, the properties of the drug itself mean there are inherent difficulties when measuring plasma concentrations; owing to the short half-life, axitinib concentrations rise and fall significantly during a dosing interval and there is minimal accumulation at steady state [13] (i.e., a concentration level that is therapeutically effective as long as regular doses are administered). In addition, axitinib degrades in the presence of light [35]; this could result in artefactual readings and the physician prescribing an incorrectly high dose of axitinib to the patient with resulting safety implications. With these limitations in mind, however, PK measurements could be considered on an individual basis, and only after checking the patient's level of compliance with treatment.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%